Employer training in Australia: current practices and concerns. (9th June 2019) - Smith, Erica; Callan, Victor; Tuck, Jacqueline; Smith, Andrew
Abstract : This paper presents and analyses results from a research project on current trends in employer training in Australia. While the formal vocational education and training (VET) system is well‐researched, the everyday training that happens in workplaces is relatively under‐researched in Australia. Using some of the results of an employer survey undertaken in 2015, the paper describes and analyses employer‐based training across a range of industry areas. The survey included groups of questions on a range of matters, including the reasons why employers train, and how these relate to employers' perceptions of their operating environment, and the structures they have in place to manage and organize training. Detailed data are provided about three specific forms of training: in‐house training and learning; the use that employers make of external providers of training; and employers' use of nationally recognised training – training from the VET system. Finally the paper reports what managers said about the barriers to providing more training. The paper analyses the findings in relation to the literature and also identified changes over time in training practices in Australian companies. Implications for training policy and practice, as well as for future research, are identified.